Corrigendum to âNumerical simulation of seismoelectric effect for monitoring foam propagation through a reservoirâ J. Petrol. Sci. Eng. 171 (2018) 618â635(S0920410518306442)(10.1016/j.petrol.2018.07.069) - Djuraev, U. (2019)
We recently published an article entitled Numerical simulation of seismoelectric effect for monitoring foam propagation through a reservoir on the Journal of Petroleum Science and Engineering 171 (2018) 618â635. The authors regret omitting explicit acknowledgement of the contributions of Dr. AndrÃ© Revil and Dr. Abderrahim Jardani, who are the authors and owners of the seismoelectric code we applied in our study. The seismoelectric code was initiated by Drs. Jardani and Revil published in (Jardani et al., 2010). The code was further developed and made available in the article by (Revil and Mahardika, 2013) and in the book by (Revil et al., 2015). Therefore, the seismoelectric code we used in the study does not belong to either to Ulugbek Djuraev, Shiferaw Regassa Jufar, Harry Mahardika or Phey Chee Ooi, who are the authors of the article. The authors would like to apologise for any inconvenience caused. Â© 2018 Elsevier B.V.